Influence of pre and postharvest applications of putrescine on ethylene production, storage life and quality of 'Angelino' plum - Khan, Ahmad; Singh, Zora (Interntional Society Horticultural Science, 2008)
The short shelf life of plum fruit limits its export to distant markets. Exogenous application of polyamines has been reported to improve fruit firmness in different plum cultivars but no information is available on the effects of putrescine (PUT) application on storage life and fruit quality (total carotenoids, vitamin C and total antioxidants) in plum. The effects of pre or postharvest PUT application on ethylene production, fruit firmness and quality of plum (Prunus salicina L. cv. Angelino) fruit during ripening after treatment, and after three or six weeks of storage, were investigated. In the first experiment trees were sprayed with an aqueous solution of PUT (0.0, 0.1, 1.0 or 2.0 mM + 0.01% Tween-20) one week before anticipated harvest and after harvest a batch of unsprayed fruit was dipped into the same PUT concentrations for 6 min. All fruit were then allowed to ripen at 20 ± 1°C. In a second experiment pre and postharvest PUT-treated fruit were stored at 0 ± 1°C and 90 ± 5% RH for three or six weeks. Irrespective of treatment method all PUT treatments delayedand suppressed climacteric ethylene production and respiration rate. In the first experiment, PUT treatments delayed fruit softening, and resulted in lower soluble solids content (SSC), total carotenoids, vitamin C and total antioxidants than the control fruit. In the second experiment, PUT-treated fruit had higher firmness and titratable acidity while SSC, total carotenoids, vitamin C and total antioxidants remained lower than the control fruit. In both experiments no differences in quality were recorded between pre- and postharvest PUT application. In conclusion, PUT (1.0mM) applied either as preharvest spray or as postharvest dip can be used to delay the ethylene production with acceptable fruit quality during ripening at ambient temperature or to extend the storage life of plum up to six weeks with minimum losses of fruit quality.